The association between negative muscle work and pedaling rate - Neptune, R. R.; Herzog, W. (Journal of Biomechanics, 1999)
The objective of this research was to use a pedal force decomposition approach to quantify the amount of negative muscular crank torque generated by a group of competitive cyclists across a range of pedaling rates. We hypothesized that negative muscular crank torque increases at high pedaling rates as a result of the activation dynamics associated with muscle force development and the need for movement control, and that there is a correlation between negative muscular crank torque and pedaling rate. To test this hypothesis, data were collected during 60, 75, 90, 105 and 120 revolutions per minute (rpm) pedaling at a power output of 260 W. The statistical analysis supported our hypothesis. A significant pedaling rate effect was detected in the average negative muscular crank torque with all pedaling rates significantly different from each other (p < 0.05). There was no negative muscular crank torque generated at 60 rpm and negligible amounts at 75 and 90 rpm. But substantial negative muscular crank torque was generated at the two highest pedaling rates (105 and 120 rpm) that increased with increasing pedaling rates. This result suggested that there is a correlation between negative muscle work and the pedaling rates preferred by cyclists (near 90 rpm), and that the cyclists' ability to effectively accelerate the crank with the working muscles diminishes at high pedaling rates.